(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Backgroud: Timing of surgery in the patients with cleft lip palate is an important factor of prognosis. Delaying in surgical repair of cleft lip and palate patient may lead to difficulty. It may causes wide, extensive and difficult dissection. There are always chances of wound infection, wound dehiscence, complete wound disruption, fistula formation, even there is also chance of maxillary hypoplasia and failure to articulate lifelong. The purpose of this study to observe the effects of cleft lip repair in early age on cleft alveolar and cleft palatal gap thus helps during cleft hard palate repair in patients with unilateral complete cleft lip and palate (UCLP). Methods: A retrospective study was done from January 2008 to July 2013. Patients with unilateral complete cleft lip and palate included in this study, who under went cleft lip at first admission and then and after 3 months of cleft palate was repaired. Patients with previous cleft lip-palate surgery were excluded. The gaps of cleft alveolus and posterior border of the cleft hard palate were recorded during 1st and 2nd operations. Age, gender, side of the cleft, associated anomalies, family history of cleft, cleft alveolar and cleft palatal gap noted, postoperative complications were also recorded. All the data were Results: A total of 63 patients included in this study. Age ranged from 4 months to 8 years. 38 patients were male and 25 were female. Right side was involved in 20 and 43 patients involved in left side. Eight patients had positive family history. Nine had associated congenital anomalies. Cleft alveolar and palatal gap reduced more in the patients who were below the age of 18 months. Postoperative complications were mild respiratory distress, notching of vermilion border developed oronasal fistula. Conclusion: In unilateral complete cleft lip palate patient, early cleft lip repair results, reduction of gaps of alveolar cleft and that of hard palate remarkably, especially in the patients who came for cleft lip surgery in appropriate time. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21023